Hans Urs von Balthasar and the question of tragedy in the novels of Thomas Hardy - Taylor, Kevin (Bloomsbury, 2013)
"What role do novels, drama, and tragedy play within Christian thought and living? The twentieth century Catholic theologian Hans Urs von Balthasar addressed these questions using tragic drama. For him, Christ was the true tragic hero of the world who exceeded all tragic literature and experience. Balthasar demonstrated how ancient, pre-Christian tragedy and Renaissance works contained important Christian concepts, but he critiqued modern novels as failing to be either truly tragic or Christian. By examining the tragic novels of Thomas Hardy on their own terms, we have an important counterpoint to Balthasar's argument that the novel is too prosaic for theological reflection. Hardy's novels are an apt pairing for examination and critique, as they are both classically and biblically influenced, as well as contemporary.The larger implication for Balthasar's theology is that his innovations in theological aesthetics and tragedy must be expanded in the light of modernity and the tragic novel." -- Publisher website
Includes bibliographical references (pages 217-229) and index
Introduction -- Balthasar and tragedy -- Balthasar's limited conception of tragedy -- Balthasar's critique of the novel and The return of the native -- The mayor of Casterbridge and prosaic reality -- Tess of the d'Urbervilles and its narrator -- Jude the obscure and ignoble suffering -- Conclusion : the place of the tragic novel within Balthasar's theology -- Bibliography -- Index
Keywords: Hardy, Thomas / 1840-1928 / Criticism and interpretation; Balthasar, Hans Urs von / 1905-1988; Hardy, Thomas -- 1840-1928; Balthasar, Hans Urs von -- 1905-1988; Tragic, The, in literature; Theology in literature; Tragik